Circumference=2πr
=2*3.14*105
=659.4cm
Answer:
Shape: Approximately Normal
Center: 20 minutes
Variability: 6.5 minutes.
Answer:
5.7
Step-by-step explanation:
3x+4 = 21
3x = 17
x = 5.666667 = 5.7
Given:
The equation is,
![2\log _3x-\log _3(x-2)=2](https://tex.z-dn.net/?f=2%5Clog%20_3x-%5Clog%20_3%28x-2%29%3D2)
Explanation:
Simplify the equation by using logarthimic property.
![\begin{gathered} 2\log _3x-\log _3(x-2)=2 \\ \log _3x^2-\log _3(x-2)=2_{}\text{ \lbrack{}log(a)-log(b) = log(a/b)\rbrack} \\ \log _3\lbrack\frac{x^2}{x-2}\rbrack=2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202%5Clog%20_3x-%5Clog%20_3%28x-2%29%3D2%20%5C%5C%20%5Clog%20_3x%5E2-%5Clog%20_3%28x-2%29%3D2_%7B%7D%5Ctext%7B%20%20%20%20%20%20%5Clbrack%7B%7Dlog%28a%29-log%28b%29%20%3D%20log%28a%2Fb%29%5Crbrack%7D%20%5C%5C%20%5Clog%20_3%5Clbrack%5Cfrac%7Bx%5E2%7D%7Bx-2%7D%5Crbrack%3D2%20%5Cend%7Bgathered%7D)
Simplify further.
![\begin{gathered} \log _3\lbrack\frac{x^2}{x-2}\rbrack=2 \\ \frac{x^2}{x-2}=3^2 \\ x^2=9(x-2) \\ x^2-9x+18=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Clog%20_3%5Clbrack%5Cfrac%7Bx%5E2%7D%7Bx-2%7D%5Crbrack%3D2%20%5C%5C%20%5Cfrac%7Bx%5E2%7D%7Bx-2%7D%3D3%5E2%20%5C%5C%20x%5E2%3D9%28x-2%29%20%5C%5C%20x%5E2-9x%2B18%3D0%20%5Cend%7Bgathered%7D)
Solve the quadratic equation for x.
![\begin{gathered} x^2-6x-3x+18=0 \\ x(x-6)-3(x-6)=0 \\ (x-6)(x-3)=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x%5E2-6x-3x%2B18%3D0%20%5C%5C%20x%28x-6%29-3%28x-6%29%3D0%20%5C%5C%20%28x-6%29%28x-3%29%3D0%20%5Cend%7Bgathered%7D)
From the above equation (x - 6) = 0 or (x - 3) = 0.
For (x - 6) = 0,
![\begin{gathered} x-6=0 \\ x=6 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x-6%3D0%20%5C%5C%20x%3D6%20%5Cend%7Bgathered%7D)
For (x - 3) = 0,
![\begin{gathered} x-3=0 \\ x=3 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20x-3%3D0%20%5C%5C%20x%3D3%20%5Cend%7Bgathered%7D)
The values of x from solving the equations are x = 3 and x = 6.
Substitute the values of x in the equation to check answers are valid or not.
For x = 3,
![\begin{gathered} 2\log _3(3^{})-\log _3(3-2)=2 \\ 2\log _33-\log _31=2 \\ 2\cdot1-0=2 \\ 2=2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202%5Clog%20_3%283%5E%7B%7D%29-%5Clog%20_3%283-2%29%3D2%20%5C%5C%202%5Clog%20_33-%5Clog%20_31%3D2%20%5C%5C%202%5Ccdot1-0%3D2%20%5C%5C%202%3D2%20%5Cend%7Bgathered%7D)
Equation satisfy for x = 3. So x = 3 is valid value of x.
For x = 6,
![\begin{gathered} 2\log _36-\log _3(6-2)=2 \\ 2\log _36-\log _34=2 \\ \log _3(6^2)-\log _34=2 \\ \log _3(\frac{36}{4})=2 \\ \log _39=2 \\ \log _3(3^2)=2 \\ 2\log _33=2 \\ 2=2 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%202%5Clog%20_36-%5Clog%20_3%286-2%29%3D2%20%5C%5C%202%5Clog%20_36-%5Clog%20_34%3D2%20%5C%5C%20%5Clog%20_3%286%5E2%29-%5Clog%20_34%3D2%20%5C%5C%20%5Clog%20_3%28%5Cfrac%7B36%7D%7B4%7D%29%3D2%20%5C%5C%20%5Clog%20_39%3D2%20%5C%5C%20%5Clog%20_3%283%5E2%29%3D2%20%5C%5C%202%5Clog%20_33%3D2%20%5C%5C%202%3D2%20%5Cend%7Bgathered%7D)
Equation satifies for x = 6.
Thus values of x for equation are x = 3 and x = 6.
$53.40 is 4lb of crab legs
Bro you just gotta multiply $13.35x4=$53.40